Determining dielectric properties of nematic liquid crystals at microwave frequencies using inverted microstrip lines. Issue 15 (8th December 2022) - Peng, Haofeng; Zhang, Yongwei; Zhu, Senlai; Temiz, Murat; El-Makadema, Ahmed
ABSTRACT: In this paper, we have investigated the dielectric properties of nematic liquid crystals (NLCs) by measuring the resonant frequencies of inverted microstrip lines (IMSLs) of NLC being the substrate material at the microwave frequency band. The designed IMSL devices consist of a cavity for NLC mixture between the inverted microstrip line and the ground plane. The anisotropy values of the NLCs were determined by observing the change of the resonant frequency when the strength of external electric fields applied on the NLCs varied. The experiments demonstrated that the effective dielectric constant of the NLC can be manipulated by the proposed devices via external bias voltage for tuning. The accuracy of the method for determining the dielectric constants of JC- M -LC-E7 (JC-E7) and QYPD-036 LCs was analysed with several prototypes based on two separate designs. The high accuracy of 91% in permittivity determination was demonstrated, and the design and fabrication techniques are beneficial for making microwave components of high tunability. Graphical abstract: uf0001